Implementation of Multimedia-assisted Collaborative Game-Based Learning to Improve Competitive Spirit and Problem Solving Ability in Literacy Learning for Elementary Students - Subrata, Heru; Judijanto, Loso; Aeni, Candra; Ali, Aisyah; Amir, Andi Subhan (FKIP Universitas Lampung, 2025)
Implementation of Multimedia-assisted Collaborative Game-Based Learning to Improve Competitive Spirit and Problem Solving Ability in Literacy Learning for Elementary Students. Objectives: This study aims to analyze the effectiveness of collaborative game-based learning assisted by multimedia in improving the competitive spirit and problem solving skills of literacy learning for elementary school students. Methods: A quantitative research approach was used, with an experimental research design. The specific design was a one-group pre-test post-test design. The research subjects consisted of 30 grade 4-6 students from an elementary school in Surabaya. Data were collected through pre- and post-test assessments to evaluate the impact of the intervention. Findings: The findings revealed that the implementation of multimedia-assisted collaborative game-based learning had a significant positive effect on students' competitive spirit and problem-solving abilities. By integrating game elements with team-based collaboration, this approach enhanced students' literacy skills while fostering critical, creative, and analytical thinking. The collaborative nature of the games allowed students to engage in healthy competition, which not only boosted their motivation but also improved their teamwork and communication skills. Additionally, students developed negotiation skills and learned how to work cooperatively to achieve common goals, which are vital social competencies. Conclusion: In conclusion, the implementation of multimedia-assisted collaborative game-based learning proved to be an effective strategy for enhancing students' competitive spirit, problem-solving skills, and literacy development. The approach, by combining game elements with collaborative efforts, effectively promoted critical thinking and enhanced social skills, making it a promising educational tool for elementary school students. This study suggests that game-based learning, supported by multimedia, can be an engaging and effective method to improve both cognitive and social outcomes in literacy education. Keywords: collaborative learning, game-based learning, literacy learning, competitive spirit, problem solving skills.